Effect of thermal cycling on the corrosion behaviour of stainless steels and Ni-based alloys in molten salts under air and argon. (15th May 2022) - Liu, Qingyang; Qian, Jiong; Barker, Richard; Wang, Chun; Neville, Anne; Pessu, Frederick
Highlight: Intermittent cooling effect during thermal cycles mitigate corrosion process in air. Tests in Ar was observed to increase CR compared to test in air. Multi-corrosion layers were observed to protect the metal and dense layer. Abstract: High temperature corrosion of materials in molten salt is of great interest to renewable energy production industry, especially the wide application of molten salts as thermal energy transfer fluid and storage media in concentrated solar power plants. Molten nitrate salt is used in concentrated solar power plants due to its good balance of thermo-physical properties and cost. Storage tanks and heat transfer pipes are widely made of corrosion resistance alloys such as austenitic stainless steels and nickel-based alloys. The corrosion issues between salt-metal interface poses a critical challenge to safety operation and efficiency. In this study, the corrosion behaviour of stainless steels and Ni-based alloys; AISI 321 and 347, IN 625 and In 825, in Solar (nitrate) salts has been experimentally investigated under isothermal (at 565 °C) and thermal cycling (between 565 °C and 290 °C) conditions, and under air and argon atmosphere. Corrosion assessment of test alloys were achieved using gravimetric measurement in a simulated metal-salt environment in a furnace for 14 days. The micro-morphology and cross-sectional analysis of the corroded surfaces were investigated by a combination of scanning electron microscopy, energy dispersive X-ray diffraction techniques. Compared with isothermal condition in air, thermal cycling in air reduces the corrosion rate of test materials, the severity of corrosion attack and the thickness of corrosion product layers due to the lower exposure time at maximum temperature and cooling effect during thermal cycling, especially in stainless steels. Compared with thermal cycling in air, the obtained corrosion rate was observed to be higher for thermal cycling in argon due to the formation of thick and fragile outer layer of NaFeO2 that easily spalls during the corrosion process. A more resilient and potentially more protective inner layer of Cr2 O3 and NiO are observed to form in stainless steels and nickel alloys respectively. The formation of intermediate layer of Fe2 O3 is believed to offer some barrier to potential molten salt induced dissolution of the inner Cr and Ni-rich layer.